Agronomic performance, genetic variability and interrelationships of grain yield and its components of selected maize (Zea mays L.) genotypes - A. Ibrahim, Hashim; S. Ibrahim, Abu Elhassan; A. Ali, Khalfala (Gezira Journal of Agricultural Science; Vol 17 No 2 (2019), 2021)
In Sudan, maize is a promising crop. It has been known and grown for a long time on small scale, under rainfed, flood and irrigated conditions. However, recently, there is increasing interest in maize production for export. In this study, 22 open pollinated genotypes introduced from International Maize and Wheat Improvement Center (CIMMYT) and Intentional Institute of Tropical Agriculture (IITA) plus two local checks (Var113, Hudieba-2) were evaluated over two seasons (2017 and 2018) and four locations, viz. New Halfa, Kassala, Gezira and Elsuki Research Station Farms of the Agricultural Research Corporation (ARC) of the Sudan. The objectives of this study were to evaluate these genotypes for grain yield and yield components and identify high yielding and stable genotypes under different environments. Treatments were arranged in a randomized complete block design with three replicates. The characters measured were days to 50% tasseling and silking, plant and ear height, ear length, number of kernel rows/ear and number of  kernels per row, ear diameter,100-kernel weight and grain yield. The study revealed significant differences among the 24 maize genotypes for most of the studied traits in each season and location separately and across them paving the road for improvement via selection. The simple linear correlation coefficient and path coefficient analysis depicted that the correlation coefficient of most traits with grain yield were significant but suggested ear diameter, ear length, number of kernels per ear and 100 kernel weight as selection criteria for grain yield improvement. Statistical analysis revealed that genotypes TZBREld-3C5, TZBR Eld-4-WC1, BR9922-DMRSR, TZBR Comp1-Y, TZEE-YPOP STR CY, 503SWAB-2, ECAQVE-6 and ECASTRIG- OFF-153 were the highest yielding across environments with a grain yield of over 2500 kg/ha. They were recommended to be grown in the favorable supplementary irrigation conditions of New Halfa, Gezira and Elsuki. The low yielding and stable genotypes of TZBREld-3C5, TZBREld-4-YC1, TZBR Comp1-W, HYDER ABAD97502 (RE) and ECASTRIGOFF-153 were recommended to be grown in the unfavorable rainfed condition of Kassala.